2016
DOI: 10.5897/ajb2015.14984
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of thermotolerant ethanol-fermenting yeasts from Laos and application of whole-cell matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF/MS) analysis for their quick identification

Abstract: Thermotolerant yeasts, which are expected to be applicable for high-temperature fermentation as an economical process, were isolated from four provinces in Laos. Of these yeasts, five isolates exhibited stronger fermentation abilities in a 16% sugars-containing medium of glucose, sucrose, sugarcane or molasses at 40°C than that of Kluyveromyces marxianus DMKU 3-1042, one of the most thermotolerant and efficient yeasts isolated previously in Thailand. One of the five strains, BUNL-17, exhibited the highest etha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
3
0
2
Order By: Relevance
“…Out of six isolated K. marxianus strains, BUNL-17 was found to be the most efficient ethanol producer at high temperature [28]. Comparison with DMKU 3-1042, which is one of most thermotolerant K. marxianus strain isolates from Thailand, revealed that BUNL-17 possesses an efficient conversion activity of xylose to ethanol, resistance to 2-deoxyglucose and tolerance to various stresses including temperature, high sugar concentration, and hydrogen peroxide [37].…”
Section: Characteristics Of Newly Isolated K Marxianus Strainsmentioning
confidence: 95%
See 2 more Smart Citations
“…Out of six isolated K. marxianus strains, BUNL-17 was found to be the most efficient ethanol producer at high temperature [28]. Comparison with DMKU 3-1042, which is one of most thermotolerant K. marxianus strain isolates from Thailand, revealed that BUNL-17 possesses an efficient conversion activity of xylose to ethanol, resistance to 2-deoxyglucose and tolerance to various stresses including temperature, high sugar concentration, and hydrogen peroxide [37].…”
Section: Characteristics Of Newly Isolated K Marxianus Strainsmentioning
confidence: 95%
“…A second isolation was attempted from similar kinds of samples described above in four provinces, Bolikhamxay, Champasak, Louang Phrabang, and Oudomxay, and 116 strains were obtained after enrichment culture as described above except that 4% ethanol was added in YPD medium. Of a total of 159 strains, 89 were identified by nucleotide sequencing of D1/D2 domains and analysis on MALDI-TOF/ MS [28]. Fermentation experiments allowed to classify them into two groups: the first bears an ethanol-fermenting ability at high temperature (116 strains) and the second the converting ability of xylose to ethanol at 37°C or more (43 strains…”
Section: Characteristics Of Thermotolerant and Ethanologenic Yeastsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perbandingan dengan beberapa hasil penilitian diantaranya Brooks (2008) yang menggunakan strain isolat Saccharomyces cerevisiae R-8 menghasilkan etanol 4.8% (b/v) dengan media fermentasi mengandung 15% glukosa pada 40 o C dan Sanchez et al (2002) menggunakan isolat C. shehatae pada media 20% glukosa pada suhu 30 o C dapat menghasilkan etanol sebesar 1.4% (b/v). Sedangkan pada isolat K. marxianus DMKU3-1042(Keo-oudone et al, 2016 menghasilkan 5.2% (b/v) dengan menggunakan media 16% glukosa pada suhu 40 o C.…”
Section: Uji Thermotolerant Dan Ethanol-tolerantunclassified
“…Pada kemampuan ethanol-tolerant, Tikka et al (2013) menyatakan jika secara umum khamir yang diuji berada pada level toleransi etanol dengan konsentrasi 0% sampai 12% (v/v). Sejauh ini khamir yang mampu untuk memfermentasi gula dan molases pada suhu 48 o C hanya khamir Kluyveromyces marxianus strain DMKU3-1042 yang diisolasi di Thailand (Limtong et al, 2007;Keo-oudone et al, 2016). Problem di industri yang memproduksi etanol yaitu kemampuan khamir jenis S. cerevisiae pada suhu 35-45 o C dan tahan konsentrasi etanol kurang dari 20% (Banat et al, 1998).…”
unclassified